Proton Irradiation on Halide Perovskites: Numerical Calculations - Alexandra V. Rasmetyeva; Stepan S. Zyryanov; Ivan E. Novoselov; Andrey I. Kukharenko; Efrem V. Makarov; Seif O. Cholakh; Ernst Z. Kurmaev; Ivan S. Zhidkov (Nanomaterials, 2023)
The results of numerical SRIM and SCAPS calculations for the ionization, displacement and heating of hybrid perovskites under the influence of protons (E = 0.15, 3.0 and 18 MeV) are presented and show that the lowest transfer energy is demonstrated by the MAPbI3, FAPbBr3 and FAPbI3 compounds, which represent the greatest potential for use as solar cells in space devices. On the other hand, it is found that perovskite compositions containing FA and Cs and with mixed cations are the most stable from the point of view of the formation of vacancies and phonons and are also promising as radiation-resistant materials with respect to powerful proton fluxes. Taking into account the lateral distribution of proton tracks showed that, at an energy level of several MeV, the release of their energy can be considered uniform over the depth and area of the entire solar cell, suggesting that the simple protection by plastic films from the low-energy protons is sufficient.